High level of full‐length cereblon mRNA in lower risk myelodysplastic syndrome with isolated 5q deletion is implicated in the efficacy of lenalidomide. (31st October 2014) - Jonasova, Anna; Bokorova, Radka; Polak, Jaroslav; Vostry, Martin; Kostecka, Arnost; Hajkova, Hana; Neuwirtova, Radana; Siskova, Magda; Sponerova, Dana; Cermak, Jaroslav; Mikulenkova, Dana; Cervinek, Libor; et al.
Abstract Downregulation of cereblon (CRBN) gene expression is associated with resistance to the immunomodulatory drug lenalidomide and poor survival outcomes in multiple myeloma (MM) patients. However, the importance of CRBN gene expression in patients with myelodysplastic syndrome (MDS) and its impact on lenalidomide therapy are not clear. In this study, we evaluate cereblon expression in mononuclear cells isolated from bone marrow [23 lower risk MDS patients with isolated 5q deletion (5q‐), 37 lower risk MDS patients with chromosome 5 without the deletion of long arms (non‐5q‐), and 24 healthy controls] and from peripheral blood (38 patients with 5q‐, 52 non‐5q‐ patients and 25 healthy controls) to gain insight into, firstly, the role of cereblon in lower risk MDS patients with or without 5q deletion and, secondly, into the mechanisms of lenalidomide action. Patients with 5q‐ lower risk MDS have the highest levels of CRBN mRNA in comparison with both lower risk MDS without the deletion of long arms of chromosome 5 and healthy controls. CRBN gene expression was measured using the quantitative TaqMan real‐time PCR. High levels of CRBN mRNA were detected in all lenalidomide responders during the course of therapy. A significant decrease of the CRBN mRNA level during lenalidomide treatment is associated with loss of response to treatment and disease progression. These results suggest that, similar to the treatment of MM, high levels of full‐length CRBN mRNA in lower risk 5q‐ patients are necessary for the efficacy of lenalidomide.